miR-488 determines coat pigmentation by down-regulating the pigment-producing gene pro-opiomelanocortin - Wang, H.; Ma, S.; Xue, L.; Li, Y.; Wang, J.; He, X.; Zhu, Z.; Dong, C. (Cellular and Molecular Biology, 2016)
Coat color is a key economic trait in wool- and fur-producing animals. Coat color is controlled by complex mechanisms. Pro-opiomelanocortin (POMC) is a gene involved in pigment formation. Previous studies suggested that miR-488 might target the POMC mRNA. This study aimed to determine whether miR-488 could affect coat color by regulating POMC and to explore the regulatory roles of miR-488 on coat color in mammals. A dual fluorescence report vector containing the 3’-UTR of POMC was built to determine whether miR-488 could post-transcriptionally regulate POMC expression. Then, a eukaryotic vector expressing miR-488 was built and transfected into mouse keratinocytes to confirm the regulatory mechanism in vitro. Compared with gray mice, the expression of POMC mRNA was 3.36-fold higher in black mice and 1.29-fold higher in brown mice. The results showed that miR-488 could control mice coat color by combining with the 3’-UTR seed sequence of POMC mRNA to achieve the degradation of POMC mRNA, therefore playing a role in POMC expression. This study revealed the roles of miR-488 in animal coat color and enriches our knowledge about the determination of coat color in mammals.